Numerical evaluation of one-dimensional large-strain consolidation of mine tailings - Agapito Tito, Luis Angel, author; Bareither, Christopher A., advisor; Shackelford, Charles D., advisor; Sutton, Sally J., committee member (Colorado State University. Libraries, 2015)
The objective of this study was to evaluate the applicability of commercially-available, one-dimensional (1-D) large-strain consolidation programs (FSConsol and CONDES0) for predicting mine tailings consolidation to estimate storage capacity of tailings storage facilities (TSFs). This study consisted of the following tasks: (i) consolidation modeling of well-known benchmark examples from literature, (ii) parametric study to assess the influence of input parameters (i.e., constitutive relationships, initial void ratio, impoundment geometry, and tailings production rate) on consolidation behavior and storage capacity, and (iii) consolidation and storage capacity prediction for a full-scale copper TSF. A benchmark example that represented instantaneous deposition of tailings (Townsend and McVay 1990) was evaluated with CONDES0 and FSConsol and indicated that both models are appropriate for predicting the consolidation behavior of tailings that are deposited instantaneously. Both models yielded similar temporal settlement curves and void ratio profiles. A gradual tailings deposition benchmark example (Gjerapic et al. 2008) was evaluated with both programs and suggested that FSConsol was more applicable for problems dealing with continuous discharge of tailings. In particular, FSConsol was more applicable when the tailings discharge rate varied temporally, which is a key constraint to modeling a full-scale TSF. The parametric study results suggested that the initial tailings void ratio and constitutive relationships (i.e., void ratio versus effective stress, e-σ', and hydraulic conductivity versus void ratio, k-e) had more pronounced effects on consolidation behavior relative to impoundment geometry and tailings production rate. In particular, a comparison between rapidly consolidating mine tailings (copper tailings) and slowly consolidating mine tailings (mature fine tailings from oil sands) indicated that a decrease in hydraulic conductivity by four orders of magnitude can extend the time required for consolidation by more than 200 yr. Changes in impoundment geometry and tailings production rate had limited effects on impoundment capacity for the range of side slopes (1.0H:1V to 4.5H:1V) and production rates (50 mtpd to 300 mtpd) evaluated in this study. FSConsol modeling results from the full-scale copper mine TSF were compared to field data and suggest that a 1-D consolidation model can yield a satisfactory prediction of in-situ consolidation behavior of copper tailings. Comparison between the actual average tailings dry density (ρd) during the first 4 yr of operation and predicted average ρd yielded coefficients of determination (R2) as high as 81 % and 93 % for Operation and Design assessments, respectively. In addition, predicted tailings height within the TSF showed good agreement with actual impoundment heights for the first 6 yr of operation; R2 = 99.1 % for the Operation assessment and cyclone operation time (COT) of 70 %, which was the average actual COT. A procedure was developed to predict average ρd of a full-scale TSF using a 1-D consolidation model that includes the following considerations: (i) estimate total tailings volume in the TSF based on predicted impoundment height and (ii) use this total volume with dry tailings mass discharged into the TSF to compute ρd. The main finding from this study was that the modeling of gradual tailings deposition with FSConsol provides a reliable prediction of impoundment height and impoundment capacity.
Keywords: consolidation; copper; mine; tailings; tailings storage facility